2017
DOI: 10.1038/s41598-017-02900-z
|View full text |Cite
|
Sign up to set email alerts
|

The malate sensing two-component system MaeKR is a non-canonical class of sensory complex for C4-dicarboxylates

Abstract: Microbial colonization of different environments is enabled to a great extent by the plasticity of their sensory mechanisms, among them, the two-component signal transduction systems (TCS). Here, an example of TCS plasticity is presented: the regulation of L-malate catabolism via malic enzyme by MaeRK in Lactobacillales. MaeKR belongs to the citrate family of TCS as the Escherichia coli DcuSR system. We show that the Lactobacillus casei histidine-kinase MaeK is defective in autophosphorylation activity as it l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
4
0
2
Order By: Relevance
“…3b). The presence of sulfate ions at the active center of RRs lacking the phosphorylatable Asp has been previously reported for MaeR triggering its phosphorylated conformation 25 . Indeed, comparing the structure of RR468 D53A with RR468 bound to BeF 3 − (PDB 3GL9) 10 confirmed that the former presented the phosphorylated conformation ( Supplementary Fig.…”
Section: Hk853-rr468 Structures Show a Ph Independentsupporting
confidence: 54%
“…3b). The presence of sulfate ions at the active center of RRs lacking the phosphorylatable Asp has been previously reported for MaeR triggering its phosphorylated conformation 25 . Indeed, comparing the structure of RR468 D53A with RR468 bound to BeF 3 − (PDB 3GL9) 10 confirmed that the former presented the phosphorylated conformation ( Supplementary Fig.…”
Section: Hk853-rr468 Structures Show a Ph Independentsupporting
confidence: 54%
“…IBR07 also contains the malolactic (MLE) and malate oxidative decarboxylase (ME) pathways, both involved in malate fermentation (Figure 3). MLE is responsible for the degradation of malate to lactate and it is encoded in a bicistronic operon regulated by the LysR‐family regulator MleR (Landete et al, 2013; Miguel‐Romero et al, 2017; Papadimitriou et al, 2016). The malolactic enzyme (MleS) is an NADP‐dependent enzyme involved in the decarboxylation of malate in a redox neutral process.…”
Section: Resultsmentioning
confidence: 99%
“…The genes of the GAS malic enzyme pathway are highly conserved and arranged as two diverging operons. MaeKR encodes the maeKR TCS, while maePE encodes a putative L-malate transporter (MaeP), and malic enzyme (MaeE) [ 88 ]. MaeKR is required for the expression of the maePE , in vitro .…”
Section: Discussionmentioning
confidence: 99%